#
SecA-1/secA+1=1-cosA/1+cosA

## Answers

Answered by

10

Answer :

Now,

L.H.S. = (secA - 1)/(secA + 1)

= (1/cosA - 1)/(1/cosA + 1), since secA = 1/cosA

= {(1 - cosA)/cosA}/{(1 + cosA)/cosA}

= (1 - cosA)/(1 + cosA)

= R.H.S. [Proved]

#MarkAsBrainliest

Now,

L.H.S. = (secA - 1)/(secA + 1)

= (1/cosA - 1)/(1/cosA + 1), since secA = 1/cosA

= {(1 - cosA)/cosA}/{(1 + cosA)/cosA}

= (1 - cosA)/(1 + cosA)

= R.H.S. [Proved]

#MarkAsBrainliest

Answered by

7

Here is the solution along with attachment

Thanks

if it helps you then please mark it as brainliest answer

Thanks

if it helps you then please mark it as brainliest answer

Attachments:

Similar questions